2019
DOI: 10.1590/1516-4446-2018-0149
|View full text |Cite
|
Sign up to set email alerts
|

Aggression directed towards others vs. aggression directed towards the self: clinical differences between intermittent explosive disorder and nonsuicidal self-injury

Abstract: Objective:To investigate the clinical differences between intermittent explosive disorder (IED) (disorder of aggression primarily directed towards others) and nonsuicidal self-injury (NSSI) (disorder of aggression predominantly directed towards the self) in order to better understand the different clinical subtypes of aggression.Methods:We used treatment-seeking samples to compare demographic and clinical correlates between 82 participants with IED and 55 participants with NSSI.Results:The IED group was older,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
(70 reference statements)
1
1
0
Order By: Relevance
“…Aggression was another factor that showed a significant effect, which is consistent with previous studies (30,31,52). Dodge et al (53) indicated that aggression factors, such as parents' aggressive behavior, gender, economic and cultural conditions, and hostile bias can result in aggressive behaviors.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Aggression was another factor that showed a significant effect, which is consistent with previous studies (30,31,52). Dodge et al (53) indicated that aggression factors, such as parents' aggressive behavior, gender, economic and cultural conditions, and hostile bias can result in aggressive behaviors.…”
Section: Discussionsupporting
confidence: 83%
“…Dodge et al (53) indicated that aggression factors, such as parents' aggressive behavior, gender, economic and cultural conditions, and hostile bias can result in aggressive behaviors. Aggressive behavior of adolescents increases due to the lack of development in advanced social skills, and especially their parents play a key role in their ability to deal with stressful situations (52). In the first author's interview, one of the participants responded that when others treat me aggressively, I repeat the same behavior.…”
Section: Discussionmentioning
confidence: 99%